Prognostic Factors for Refractory Status Epilepticus - J. Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Researchers at the Mayo Clinic, Rochester, MN studied the outcome and identified prognostic factors for refractory status epilepticus (RSE) in 54 adult patients, median age 52 years [range 18-93].